PEMBERDAYAAN DINAS SOSIAL KOTA PEKANBARU DALAM MELAKSANAKAN REHABILITASI ANAK JALANAN TAHUN 2021-2022 - Ramadani, Putri Sari; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The government is the people who have the authority to process public services and are obliged to process civil services for everyone who has government relations, in this case the government has 4 functions, namely regulation, service, empowerment and development. Rehabilitation is a manifestation of one of the main tasks of regional governments and their apparatus, namely empowering the community. Social rehabilitation is one of the tasks of the Pekanbaru City Social Service in improving protection and social rehabilitation services for street children. The problem in this research is that the high number of street children in Pekanbaru City requires serious rehabilitation empowerment activities from the Pekanaru City Social Service to reduce the number of street children. The negative stigma that has emerged has an impact on street children who are considered nuisances in society. In addition, there are no strict sanctions for street children who return to the streets after being rehabilitated. This research aims to describe and determine the factors inhibiting the Empowerment of the Pekanbaru City Social Service in Carrying out Rehabilitation for Street Children in 2021-2022. This research is descriptive research with a qualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data that supports or strengthens primary data and data collection techniques are carried out by means of interviews and documentation. The results of the research show that in carrying out the task of social rehabilitation for street children in 2022, namely by providing street children with rights such as providing assistance with population administration rights, the shelter as a place for social rehabilitation carried out by the Pekanbaru City Social Service can be used as a halfway house for children. Streets, there they are cared for, given food, clothing and shelter. In fulfilling the need for further rehabilitation, the Pekanbaru City Social Service collaborates with Lembaga Sentra Abiseka and UPT PSBR Marsudi Putra Tengkuyuk. Keywords: Government, Community Empowerment, Social Rehabilitation, Street Children.